Prevalence of Haemonchus contortus in Goats of Western Chitwan of Nepal - Adhikari, Kashyap; Rana, Hari Bahadur; Kaphle, Krishna; Khanal, Tanka; Raut, Rabin (International Journal of Applied Sciences and Biotechnology, 2017)
The research was done in cross sectional design to study about the prevalence of Haemonchus contortus in goats of Western Chitwan of Nepal. A total of 252 fecal samples were collected through purposive sampling. Fecal samples were examined through sedimentation and floatation method. Egg per gram (EPG) was calculated through Mac Master Counting Technique of positive samples. Total prevalence was found to be 13.89%. Infection of parasite was more prevalent in males (15.18%) than in female (12.86%) but was statistically non-significant (P>0.05). In non-dewormed goats (40.32%), the prevalence was significantly (P<0.05) higher than in dewormed goats (5.26%). The results regarding the relationship between different age groups of goats and H. contortus showed that highest prevalence (14.54%) of parasite was observed in age group of below 1 year and the lowest (12.96%) in age group of above 2 year, statistically non-significant (P>0.05). Maximum goats were found with medium level of infestation through EPG. This study shows higher prevalence of Haemonchus in non-dewormed than in dewormed goats which is statistically significant at (P<0.05). Thus, effective deworming programme and management must be maintained in order to upgrade the health status and maximize the benefits from the animal. Int. J. Appl. Sci. Biotechnol. Vol 5(3): 321-325